ANALISIS PENGARUH DAYA TARIK PESAN IKLAN, PERSEPSI KEMANFAATAN, CITRA MEREK PADA MEDIA SOSIAL TWITTER TERHADAP PEMBENTUKAN BRAND AWARENESS (Studi Kasus pada Media Sosial Twitter @infoUNDIP atau Info Undip Media) - Andika Putra, Afif Raihan; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2014)
This study was conducted to analyze the factors that influence the formation of brand awareness on social media case study on the twitter info Undip media or social media twitter @infoUNDIP . The problems of this research is the shift of the conventional media to digital media department also driven by cost more light on digital media so that more dpertimbangkan and taken into account . Independent variable in this research consists of Fascination Advertising Messages ( X1 ) , Perceived usefulness ( X2 ) , and brand image ( X3 ) and variable dependent is Brand Awareness ( Y ) .The sample of 100 respondents were taken using purposive sampling technique . Analysis using the SPSS 16.0 includes , reliability test , validity test , the classic assumption test , multiple regression analysis , hypothesis testing via the F test and t test , and analysis of the coefficient of determination ( R Â² ) .Perception of usefulness showed the greatest regression coefficient . Perception of usefulness is the most important factor that affects the formation of brand awareness on social media twitter . The second important factor is the Fascination Book Brand Image Advertising later as the third factor that affects the formation of brand awareness on social media twitter . The coefficient of determination ( adjusted R2 ) of 0.449 , or 44.9 percent of the coefficient of determination means the model is good enough . All three independent variables in this study can explain 44.9 percent of the variable brand awareness . While the remaining 55.1 percent is explained by other variables outside of the three variables used in this study .